Trade liberalization, employment flows and wage inequality in Brazil - Francisco H. G. Ferreira; Phillippe G. Leite; Matthew Wai-Poi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Using nationally representative, economy-wide data, this paper investigates the relative importance of trade-mandated effects on industry wage premiums; industry and economy-wide skill premiums; and employment flows in accounting for changes in the wage distribution in Brazil during the 1988-95 trade liberalization. Unlike in other Latin American countries, trade liberalization appears to have made a significant contribution towards a reduction in wage inequality. These effects have not occurred through changes in industry-specific (wage or skill) premiums. Instead, they appear to have been channelled through substantial employment flows across sectors and formality categories. Changes in the economy-wide skill premium are also important.
Keywords: D31; F16; J31; 330; trade liberalization; inequality; employment flows; Brazil; Außenhandelsliberalisierung; Industrielohn; Lohnstruktur; Einkommensverteilung; Industrielle Beschäftigung; Brasilien